2020
DOI: 10.1108/tg-12-2019-0122
|View full text |Cite
|
Sign up to set email alerts
|

Core – competencies – a key to future – oriented and sustainable e-governance implementation: a mixed method research

Abstract: Purpose The purpose of this paper is to empirically identify the themes of core-competencies required for future-oriented and sustainable e-governance practices, especially across the developing nations. Design/methodology/approach The present study has been conducted using the sequential mixed method research wherein the exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 104 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…It witnessed that corruption is a global issue and a threat to state development and progress (Moschovis, 2010; Rose and Peiffer, 2015). It examined that ICT inclusion reduces and controls corruption practices in developing countries (Hooda and Singla, 2021; Marchini et al , 2020). There is a rich literature on corruption or institutional corruption in Asia, Africa and other developing and developed regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It witnessed that corruption is a global issue and a threat to state development and progress (Moschovis, 2010; Rose and Peiffer, 2015). It examined that ICT inclusion reduces and controls corruption practices in developing countries (Hooda and Singla, 2021; Marchini et al , 2020). There is a rich literature on corruption or institutional corruption in Asia, Africa and other developing and developed regions.…”
Section: Discussionmentioning
confidence: 99%
“…They found it compelling and sustainable in enhancing institutional performance and transparency. Moreover, Hooda and Singla (2021) and Marchini et al (2020) observed that ICT inclusion effectively controls the effects of corruption and enhances public service integrity and transparency.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They found it appealing and long-lasting to improve institutional performance and openness. In addition, Hooda and Singla [ 54 ] and Marchini, Mazza, and Medioli [ 55 ] noted that ICT integration reduces the negative impacts of corruption and improves the integrity and transparency of the public sector.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They stated that cybersecurity threats might be successfully countered by considering socio-economic variables. Researchers have examined security threats to public institutions and their risk management practices in developed and emerging Asian and European countries by focusing on the SDGs and secure ICT networks [ 54 , 61 ]. They examined how cybersecurity safeguards and ICT standards benefit established and emerging economies’ e-government systems.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%